2020
DOI: 10.1097/jcma.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Better endovascular mechanical thrombectomy outcome in atrial fibrillation patients with acute ischemic stroke: A single-center experience

Abstract: Background: Endovascular thrombectomy (EVT) has become the standard treatment for acute ischemic stroke with large vessel occlusion. Atrial fibrillation (AF) is one of the major causes. However, the impact of AF on the treatment has not yet been clearly discussed. This study is to evaluate the influence of AF on the outcomes of EVT in patients with acute ischemic stroke. Methods: Data from our Stroke Registry Database from April 2015 to July 2018 were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…Outcome data of patients with AF who undergo EVT are less established. Our findings are supported by a recent meta-analysis, which reported higher rates of mRS 0-2 in AF patients after EVT [18] . In addition, other smaller registry studies have found similar results, suggesting improved reperfusion rates and good functional outcome in EVT patients with AF [13,19] .…”
Section: Discussionsupporting
confidence: 90%
“…Outcome data of patients with AF who undergo EVT are less established. Our findings are supported by a recent meta-analysis, which reported higher rates of mRS 0-2 in AF patients after EVT [18] . In addition, other smaller registry studies have found similar results, suggesting improved reperfusion rates and good functional outcome in EVT patients with AF [13,19] .…”
Section: Discussionsupporting
confidence: 90%
“…This may be related to the nursing care of postoperative patients in our hospital and could be improved in the future. Numerous studies have confirmed that age is significantly associated with the prognosis of acute stroke patients (12,21,22). This current study further confirmed the important role of age in the unsatisfactory outcomes and in-hospital mortality.…”
Section: Discussionsupporting
confidence: 87%
“…An additional 2 studies were identified via expert recommendation. Finally, 10 studies [14][15][16][17][18][19][20][21][22][23] with 6543 patients were determined to satisfy our inclusion criteria with the appropriate report of outcomes of interest (eFigure 1 in Supplement 1).…”
Section: Search and Screening Resultsmentioning
confidence: 99%